Accounting and Politics in Europe: Influencing the Standard. (1st September 2020) - Walton, Peter
ABSTRACT: The paper considers the case of lobbying to influence the content or other aspects of a standard within Europe. It reviews the institutional framework to identify opportunities for lobbying and then considers the mechanics and constraints that affect lobbying in this context.